UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA MATERI BARISAN DAN DERET MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TRADE A PROBLEM SISWA KELAS XI MIPA 1 SMAN 7 DENPASAR TAHUN PELAJARAN 2022/2023 - Ketut Widyarin Sulastra (Widyadari, 2023)
The Trade a Problem type cooperative model is a model where students are asked to write questions and answers for topics assigned by the teacher, then they exchange their questions with other groups. The purpose of this study was to increase the activity and learning outcomes of mathematics by using the Trade a Problem learning model for students’ sequences and series material. The research subjects were students of class XI MIPA 1 at SMAN 7 Denpasar for the 2022/2023 academic year. Research object activeness and student learning outcomes. This type of research is classroom action research. The stages of this research consisted of pre-cycle, cycle I, and cycle II. For each cycle consists of planning, implementation, observation and reflection. The results showed that in the pre-cycle the average student activeness was 52% and the average learning outcomes was 69.75 with a complete learning of 64.58%, in the first cycle the student learning activeness was 60.5% and the average student score achieved 74.52 with 81.25% classical completeness, in cycle II there was an increase in learning activity to 73.5% and the average student score reached 79.96 with 93.75% classical completeness. The conclusions from this study indicate that the use of the Trade a Problem cooperative learning model in learning mathematics can increase the activity and learning outcomes of class XI MIPA 1 students at SMAN 7 Denpasar.